SASTRA BANDINGAN CERITA “CINDERELLA” DAN CERITA “YEH-SHEN”: MANFAAT CERITA RAKYAT BAGI ANAK - Safitri, Novi Karlinda (Universitas Pakuan, 2024)
Comparative literary studies aim to compare two literary works to reveal the similarities and differences contained in the two literary works. Comparative literary studies can be used to compare two literary works from two different places. One of the popular literary works to compare nowadays is folklore. The Cinderella folklore and the Yeh-Shen folklore come from different countries but have similar story. In this way, this research discusses the similarities and differences between the Cinderella folklore popularized by the Grimm Brothers and the Yeh-Shen folklore which is popular in China. This research aims to describe the similarities and differences between the Cinderella and the Yeh-Shen folklores by comparing the intrinsic elements of the two folklores. The study used in this research is a structural study of comparative literature. This research uses a descriptive-comparative method. The theories used are intrinsic theory and comparative literary theory. These results and discussion show that 1) there are similarities and differences between the folklores Cinderella and Yeh-Shen in the intrinsic elements of theme, plot, characters and setting. 2) there are four benefits from the two folklores. Key words: comparative literature, children's literature, folklore, structural